Changes in audiovisual narrative practices in post-media era (Comunicação & Inovação, 2016)
The purpose of this study is to investigate the differences in the practices of production, display and transmission betweencommunity videos made by social movements activists in the late 1980s and internet transmissions made by the free media in the June 2013 street protests in Rio de Janeiro. We will analyze in which way they manifest themselves in alternative communication practices and how they affect the subjectivity of the activists from the 1980s and the activists of free media in the beginning of the 21th century.
Keywords: Subjectivity. Post-media. Media activism.